ANALISIS EKO-EFISIENSI PADA USAHA KECIL DAN MENENGAH (UKM) BATIK LARISSA KOTA PEKALONGAN - Alifa Noor Amelia; Bulan Prabawani (Universitas Diponegoro, 2019)
Eco-efficiency is a concept that incorporates aspects of natural resources and energy by minimizing the use of raw materials, water, energy and the resulting environmental impacts. This study aims to determine the application of eco-efficiency in Batik Tulis SMEs in Batik Larissa. The study used descriptive analytical methods with a qualitative approach. Data collected through observation, in-depth interviews and literature studies. Observations were focused on the consumption of energy, material, and water to find out the difference between before and after the implementation of the eco-efficiency concept. In one week Larissa Batik produces 9 pieces of Batik Alus and 80 pieces of cotton batik through disconnected consignment with home workers. In one week they produces 9 pieces of Batik Sutera and 80 pieces of Cotton Batik. The accumulation of NPO costs per year before the implementation of eco-efficiency amounted to Rp 33,103,499.52 with an NPO ratio and production costs of 2.58%. They has implemented several eco-efficiency concepts by reducing the use of, reducing environmental pollution and enlarging product recycling After applying the eco-efficiency concept, they received an economic profit of Rp. 29,298,651.72 per year with a ratio between NPO costs and production costs decreased to 1.8% per production.